THE ISSUE OF MEDIA STYLISTICS IN MODERN LINGUISTICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In modern linguistics, there has been a "media turn", which allows you to take a fresh look at the old linguistic problems and open up new horizons for innovative theories. Media linguistics today begins to take a leading place in scientific research. the term media linguistics almost pushed out to the periphery the previously existing term media language. This article explains the issue of media stylistics in modern linguistics